Whistling past the graveyard - Crandall, Susan (Gallery Books, 2013)
"In the summer of 1963, nine-year-old spitfire Starla Claudelle runs away from her strict grandmother's Mississippi home. Starla hasn't seen her momma since she was three--that's when Lulu left for Nashville to become a famous singer. Starla's daddy works on an oil rig in the Gulf, so Mamie, with her tsk-tsk sounds and her bitter refrain of 'Lord, give me strength, ' is the nearest thing to family Starla has. After being put on restriction yet again for her sassy mouth, Starla is caught sneaking out for the Fourth of July parade. She fears Mamie will make good on her threat to send Starla to reform school, so Starla walks to the outskirts of town, and just keeps walking. ... If she can get to Nashville and find her momma, then all that she promised will come true: Lulu will be a star. Daddy will come to live in Nashville, too. And her family will be whole and perfect. Walking a lonely country road, Starla accepts a ride from Eula, a black woman traveling alone with a white baby. The trio embarks on a road trip that will change Starla's life forever. She sees for the first time life as it really is--as she reaches for a dream of how it could one day be."